A Simplified Nonlinear Generalized Maxwell Model for Predicting the Time Dependent Behavior of Viscoelastic Materials - Monsia, Marc Delphin (My University, 2011)
In this paper, a simple nonlinear Maxwell model consisting of a nonlinear spring connected in series with a nonlinear dashpot obeying a power-law with constant material parameters, for representing successfully the time-dependent properties of a variety of viscoelastic materials, is proposed. Numerical examples are performed to illustrate the sensitivity of the model to material parameters
Keywords: Hyperlogistic-Type Function; Maxwell Model; Nonlinear Stress-Time Relationship; Riccati Equation; Viscoelasticity